New Developments in Virtual Reality-Assisted Treatment of Aggression in Forensic Settings: The Case of VRAPT - González Moraga, Fernando Renee; Klein Tuente, Stéphanie; Perrin, Sean; Enebrink, Pia; Sygel, Kristina; Veling, Wim; Wallinius, Märta (Frontiers in Virtual Reality, 2022)
Aggression is a known problem in individuals being cared for in forensic settings, yet the evidence base for its treatment is scarce. Virtual Reality (VR) has been proposed as a promising addition to interventions in forensic settings, as it may increase the motivation among participants, bridge the gap between real life, therapeutic and laboratory experiences, and increase the ecological validity of psychological research. Recently, a new treatment for aggression using VR as the treatment environment, Virtual Reality Aggression Prevention Training (VRAPT) program, was developed to provide realistic and safe environments for participants to practice aggression management. In its current revised version, VRAPT is conceptualized as a form of cognitive behavioral therapy with its theoretical background in the General Aggression Model. Its purpose is to increase awareness of, and improve control over, one's own aggression and that of others through social interactions in individually tailored virtual environments. This manuscript describes how the lessons learned from the first randomized controlled trial of VRAPT have been applied to further develop the method and discusses challenges and future directions for VR-assisted treatment of aggression in forensic settings. VRAPT is a new psychological treatment for aggression and the coming years will provide expanded scientific evidence for further developments and adaptations.